OPINION LEADER'S COMMUNICATION PATTERNS IN STRENGTHENING A GREEN ECONOMY THROUGH MSMEs IN SERANG CITY, BANTEN INDONESIA - Sigit Surahman; Yudhistira Ardi Poetra (International Journal of Social Science, 2022)
Micro, Small Medium Enterprise (MSMEs) is a general term that refers to productive economic businesses owned by individuals or business entities in accordance with the criteria stipulated by Law no. 20 of 2008. The pattern of integrated communication between leaders and the community is essential to accommodate the food self-sufficiency program as a green economy. The focus of this study describes how the communication pattern of opinion leaders is appropriate for the empowerment of MSMEs in the success of the green economy. The goal is to build a better communication pattern between leaders and the community of MSME actors in facing the challenges of the green economy. The research uses a case study paradigm with a qualitative approach. The research subjects are opinion leaders, the community, and local stakeholders. The location is MSMEs in Terondol Village, Serang, Banten, Indonesia. The results show that the communication pattern between the leaders and the community of MSMEs actors is with a more focused mentoring communication model from opinion leaders and stakeholders in developing more democratic group communication to its members. Top-down and bottom-up linear communication patterns need improvement and strengthening in order to provide correct understanding in communicating and developing MSMEs.